2019
DOI: 10.1111/apt.15551
|View full text |Cite
|
Sign up to set email alerts
|

Masked bolus gluten challenge low in FODMAPs implicates nausea and vomiting as key symptoms associated with immune activation in treated coeliac disease

Abstract: Summary Background In patients with coeliac disease, FODMAPs in gluten‐containing foods, and participant anticipation of a harmful (‘nocebo’) effect, may contribute to acute symptoms after gluten challenge. Aim To establish acute gluten‐specific symptoms linked to immune activation in coeliac disease Methods We included 36 coeliac disease patients on a gluten‐free diet receiving placebo in the RESET CeD trial. Double‐blind, bolus vital wheat gluten (~6‐g gluten protein) and sham challenges low in FODMAPs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 25 publications
1
47
1
Order By: Relevance
“…In the three phase 1 studies, which have been reported in detail elsewhere, patients with coeliac disease were maintaining their usual gluten‐free diet had no study interventions before their pre‐treatment biopsy. In the phase 2 (‘RESET CeD’) trial, which has also been described elsewhere, patients with coeliac disease were maintaining their usual gluten‐free diet, but had a single bolus gluten challenge (6 g of gluten protein taken as 10 g vital wheat gluten flour in water) 3 weeks before biopsy collection according to the protocol described by Tye‐Din et al…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the three phase 1 studies, which have been reported in detail elsewhere, patients with coeliac disease were maintaining their usual gluten‐free diet had no study interventions before their pre‐treatment biopsy. In the phase 2 (‘RESET CeD’) trial, which has also been described elsewhere, patients with coeliac disease were maintaining their usual gluten‐free diet, but had a single bolus gluten challenge (6 g of gluten protein taken as 10 g vital wheat gluten flour in water) 3 weeks before biopsy collection according to the protocol described by Tye‐Din et al…”
Section: Methodsmentioning
confidence: 99%
“…All patients gave written, informed consent prior to undergoing any trial‐related procedures. Eligibility criteria for each clinical trial have been reported fully elsewhere . In brief, for all four studies, patients who had biopsies collected had met initial screening criteria, which included being aged between 18 and 70 years, having documented duodenal villus atrophy while consuming gluten, being positive for HLA‐DQA1*05 and DQB1*02 (‘HLA DQ2.5’), and having maintained a gluten‐free diet for at least 1 year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include nocebo effects, where patient's negative expectations to potential gluten exposure influence their symptoms and the presence of non-gluten dietary components such as fermentable carbohydrates (FODMAPs) that can cause symptoms of irritable bowel syndrome (IBS) independent of gluten [4,5]. In several recent gluten food challenge studies in small groups of patients with treated CD, unmasked and also double-blind, sham-controlled gluten challenges designed to be low in FODMAPs cause significant worsening of nausea, sometimes with vomiting, within 2-h and peak at 3 to 4 h, but rarely caused diarrhoea [6,7]. This acute symptomatic reaction to gluten in patients with treated CD is linked to significant concomitant elevations in serum cytokines, which are not observed in individuals without CD or those with self-reported non-CD gluten sensitivity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The condition is becoming increasingly diagnosed and is estimated to affect 2% of many ethnically diverse populations ( 5 , 6 ). Strict compliance with a gluten-free diet is the only effective treatment, but the diet is inconvenient and expensive, and inadvertent gluten exposures are common ( 7 ), which can cause debilitating symptoms such as vomiting, diarrhea, and diminished well-being ( 8 ).…”
Section: Introductionmentioning
confidence: 99%